Segmental Stiff Skin Syndrome: A Rare Case Report from Indonesia - Nurmastuti, Hafidzah; Danarti, Retno; Anggraheni, Radijanti; Arvianty, Intan; Susetiati, Devi Artami; Trisnowati, Niken (Faculty of Medicine, Universitas Airlangga, 2025)
Background: This paper reports a segmental Stiff Skin Syndrome (SSS) case in a four-year-old girl. SSS is a rare disease characterized by skin hardening and joint stiffness due to a mutation of the fibrillin-1 (FBN-1) gene encoding the fibrillin protein. The effective therapies for this disease are limited. Case Report: The patient presented with hardened skin and a limping gait. Clinically, there were hard, hyperpigmented patches with hypertrichosis on the skin of the left femur and left gluteal. The left coxae and left genu joint were in fixed flexion, causing a limping gait. The SSS histology revealed thickened collagen fibers, trapping adipocytes between them, but no inflammatory cells. The UV-A phototherapy and physiotherapy session resulted in a modest improvement. Discussion: This case's segmental SSS diagnosis was based on clinical and histological findings. Establishing a diagnosis of SSS is a challenge for clinicians because it can resemble other skin disorders, particularly sclerosing diseases. The recommended management for SSS remains limited. In this case, after the UV-A phototherapy and physiotherapy, complaints of hardened skin were said to soften.